Prevalence and socio-demographic determinants of depression among inmates of a prison in Malaysia - Subbarao, Gunenthira Rao; Minhat, Halimatus Sakdiah; Kadir @ Shahar, Hayati; Mukhtar, Firdaus; Subbarao, Anusuyah (Light House Polyclinic, 2019)
Depression is the most common form of mental disorder among prison inmates. The objective of this study is to determine the prevalence and socio-demographic determinants of depression among adult male inmates in a local prison in Malaysia. This cross-sectional study was conducted among 460 inmates who were systematically selected. Depression was screened using the Center for Epidemiologic Studies Depression (CES-D) scale. Chi-square tests and multiple logistic regression were applied to determine the association between depression and associated variables. Data was analyzed using SPSS software with a p value less than 0.05 was considered significant. The response rate was 90.7% while prevalence of depression was 40.7%. The presence of communicable disease (AOR=2.249, 95%Cl=1.217-4.156) and non–communicable disease (AOR=1.890, 95%Cl=1.132-3.156) identified as socio-demographic determinants of depression. The study suggest a high prevalence of depression among the inmates. Initiative must be given to address and improve the prison health care services.